Performance Improvement of Unit IV Intelligence and Security Unit Karanganyar Resort Police in Operational Intelligence Activities to Prevent the Impact on Social Security and Order from the Use of Gedongan Village’s Treasury Land - Arviano Gatra Aditya (Advances in Police Science Research Journal, 2024)
Implementation of operational intelligence activities by Unit IV Intelligence and Security Unit Karanganyar Resort Police in order to prevent impacts caused by misuse of the utilization of Gedongan Village’s Treasury Land, it is necessary to do some performance improvement because there are still many deficiencies in the operational intelligence activities both from organizational resources and works systems. Writing of this Final Exam using a qualitative descriptive research method with data collection techniques by interview, observation and document study. The theory used to find comparisons between factual and ideal conditions is management theory, Seven Steps Operational Management, as well as using the concepts of performance improvement, Intelligence and Security Unit, Operational Intelligence Activities, preventing impacts, and utilizing Village Treasury Land. The results of the research carried out that in the implementation of Operational Intelligence Activities by Unit IV Intelligence and Security Unit of the Karanganyar Resort Police in order to prevent the impacts of Social Security and Order on the use of Gedongan Village’s Treasury Land from a management perspective has not run optimally because there are still deficiencies found in terms of organizing, implementing and supervising it, as well as human resources organization namely human resources, budget, and infrastructure. The conclusion obtained is that the performance of Unit IV Intelligence and Security Unit of the Karanganyar Resort Police in carrying out operational intelligence activities to prevent impacts of Social Security and Order on the utilization of the Gedongan Village’s Treasury Land has not been maximized with problems of lack of personnel, lack of operational budgets, and supervision of the implementation of activities that are not in accordance with the applicable of Procedure Operational Standard, so as to improving the performance of the Karanganyar Resort Police’s Unit IV Intelligence and Security Unit can be in the form of coordinating with other functions, implementing a priority system in budget absorption, as well as promoting the production of intelligence products.